“Desain Dan Analisa Bidirectional Inverter Sebagai Penggerak Mesin Induksi Satu Fasa Dengan Sumber Baterai DC 36 Volt ” - Aulia, Abi Yusuf; Hamzah, Amir; Nurhalim, Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Increasing oil prices and global warming, many people think to developed energy technology. One of them is the bidirectional DC-DC / DC-AC converter. Bidirectional that mean the converter can work in both directions. In this journal, the writer proposed bidirectional DC/AC inverter. Bidirectional inverter is an inverter that works in both directions. Which can convert AC input into a DC output or otherwise. In this paper discusses a single phase AC induction machine can rotates when fed DC voltage from the battery. And at the time of Induction Machines apply a voltage from utility (PLN), the battery can be charged. Bidirectional switching inverter using PWM mode. Bidirectional inverter modeling is simulated by using software MATLAB / Simulink.Keywords : Energy Technology, Bidirectional Inverter, PWM, MATLAB